CONTRIBUTION OF RIPARIAN POPULATIONS TO THE SUSTAINABLE DEVELOPMENT OF FISHING IN THE WESTERN SECTOR OF THE ÉBRIÉ LAGOON - KOFFI , Kouadio Jacques; SEKONGO , Largaton Guénolé; KOUADIO, Nanan Kouamé Félix (Revue Internationale du Chercheur, 2025)
Abstract This article, entitled "Contribution of Local Communities to Sustainable Fishing Development in the Western Sector of the Ebrié Lagoon," aims to demonstrate the strategies adopted by local communities to boost production and sustain fishing activities in the western sector of the Ebrié Lagoon. The methodology adopted for data collection is based on observation, documentary research, and fieldwork. The survey was conducted among 230 fishermen, village authorities, and management committee leaders from the various villages visited (Songonté, N'gatty, Tiaha, Dabouli, Gboyo, Taboutou, and N'djem). The results showed that local residents' awareness of the importance of organizing fishing activities has led them to take initiatives such as the creation of lagoon bays, the grouping of stakeholders into GVCs, the establishment of biological rest periods, and the use of traditional methods, all of which are conducive to sustainable fishing. These initiatives, while considered a genuine source of hope for sustainable fishing development, fall far short of meeting the expectations of local residents due to the large and uncontrolled number of illegal fishermen using prohibited gear and methods (small-mesh nets, toxic products, etc.).